1996
DOI: 10.1046/j.1365-2826.1996.04473.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Galanin mRNA in GnRH Neurons by Estradiol and its Facilitation by Progesterone

Abstract: On the day of proestrus in the rat, rising plasma levels of estradiol (E) act in concert with progesterone (P) to trigger a preovulator y release of gonadotropins. Cellular levels of galanin mRNA in GnRH neurons are increased in association with the proestrous surge of gonadotropin secretion; however, the relative contribution made by E and P to the induction of galanin mRNA expression in GnRH neurons is unknown. We investigated the role of E and P in the induction of galanin gene expression in GnRH neurons by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…As the rats were treated with estradiol alone or both estradiol and progesterone, the galanin mRNA expression in the GnRH cells was increased about 3-fold or 5-fold respectively compared with vehicle-treated animals [146]. Last, on the day of proestrus progesterone facilitated galanin mRNA expression in GnRH cells and the LH surge triggered by estradiol-induced positive feedback signals [146]. In turn, galanin may markedly stimulate progesterone release from cultured granulosa cells.…”
Section: The Relationship Between Galanin and Gonadal Hormonementioning
confidence: 99%
“…As the rats were treated with estradiol alone or both estradiol and progesterone, the galanin mRNA expression in the GnRH cells was increased about 3-fold or 5-fold respectively compared with vehicle-treated animals [146]. Last, on the day of proestrus progesterone facilitated galanin mRNA expression in GnRH cells and the LH surge triggered by estradiol-induced positive feedback signals [146]. In turn, galanin may markedly stimulate progesterone release from cultured granulosa cells.…”
Section: The Relationship Between Galanin and Gonadal Hormonementioning
confidence: 99%
“…Previous work has reported that hypothalamic galaninergic gene expression varies with oestrus cycle stage (Brann et al 1993, Rossmanith et al 1996, Finn et al 1998, Tourlet et al 2005) and/or is affected by steroids (Tourlet et al 2005). Using a targeted approach, the results of this study suggest that galanin mRNA expression changes over the oestrous cycle, in a region-specific manner (mPOA/OVLT, PVN, ARC but not mPOA), conducive with localised actions.…”
Section: Discussionmentioning
confidence: 50%
“…That study, however, used immunocytochemistry and it is possible that more localised transitory changes in expression could have been missed. Elevated galanin expression during the follicular phase has previously been reported in rodents (Brann et al 1993, Rossmanith et al 1996, Finn et al 1998) and in one study on sheep in which galanin expression was assessed as the number of detectable immunoreactive cells (Tourlet et al 2005). While Tourlet et al (2005) reported changes in ovine galanin expression within the POA but not in the BNST or infundibular nucleus in response to an E 2 signal, comparison of the anatomical data indicates that the stimulatory effects on galanin immunoreactive cells corresponds with the increase in mRNA expression seen in the mPOA/OVLT in the current study, with little effect in the more rostral regions of the POA.…”
Section: Discussionmentioning
confidence: 77%
“…A similar effect of ovarian sex steroids on the induction of galanin mRNA has been reported in the rat central nervous system (Rossmanith et al 1996). According to Rossmanith et al, was the primary ovarian signal inducing galanin mRNA expression in gonadotrophin-releasing hormone (GnRH) neurons.…”
Section: Discussionmentioning
confidence: 58%
“…According to Rossmanith et al, was the primary ovarian signal inducing galanin mRNA expression in gonadotrophin-releasing hormone (GnRH) neurons. In addition, progesterone facilitated the action of oestradiol-17 on galanin gene expression in GnRH neurons (Merchenthaler et al 1991, Rossmanith et al 1996. It has also been reported that galanin neurons exhibit oestrogen receptors in the rat hypothalamus (Horvath et al 1995).…”
Section: Discussionmentioning
confidence: 85%